Identification of Dermatoglyphic Patterns in Parents of Children with Cystic Fibrosis - Hamid Reza Kianifar (International Journal of Pediatrics, 2018)
Background Dermatoglyphics could assist in the diagnosis of congenital abnormalities. The aim of this study was to identify the dermatoglyphic patterns (finger print pattern type, total ridge count of each finger, a-b ridge count, and articulotrochanteric distance [ATD angles]) in the parents of cystic fibrosis children. Materials and Methods We recruited 75 parents of children with cystic fibrosis for the study group and 341 parents for the control group. We recorded finger print pattern type, total ridge count (TRC), a-b ridge count, and ATD angles of all participants. Then we identified any asymmetry between the right and left hands of each person and characteristics of parents in two genders. Chi-square analysis, Mann-Whitney U test, and Fisher's exact test were used for data analysis. Results We observed significant differences in a-b ridge count on the right hand (P=0.02), and mean total ridge count on the right digit I (P=0.05), right digit IV (P=0.03), and right digit V in  the fathers of children with cystic fibrosis compared to the control group(P=0.02). Conclusion According to the results, we suggest that the dermatoglyphic traits of parents could be used as a simple, appropriate, and supplementary screening method in the diagnosis of children with CF. Nevertheless, we need lager studies to precisely confirm that dermatoglyphics is a reliable method in the diagnosis of CF.